Correlation of GLUT4, LEPR, and TNF-α with endometrial receptivity in women with polycystic ovarian syndrome-induced infertility - Dong, Yan; Kong, Wei; Li, Yifei; Liu, Yan; Li, Lin; Li, Yan (Journal of Medical Biochemistry, 2024)
Objective: To analyze the correlation of glucose transporter 4 (GLUT4), leptin receptor (LEPR) and tumor necrosis factor-α (TNF-α) with endometrial receptivity in patients with polycystic ovarian syndrome (PCOS)-induced infertility, so as to provide clinical evidence for future diagnosis and treatment of PCOS-induced infertility. Methods: Forty-two patients with PCOS-induced infertility admitted to our hospital from June 2020 to August 2023 (research group), as well as 35 concurrent cases of simple PCOS (control group) and 32 healthy women (normal group) were selected as the research participants. Peripheral blood GLUT4, LEPR and TNF-α levels were detected in all participants, and the diagnostic value of the three for PCOS in healthy women and for PCOS-induced infertility in PCOS patients was analyzed. In addition, the endometrial thickness and the endometrial blood flow pulsation index (PI) and resistance index (RI) of patients in the research group were measured, and the correlation of GLUT4, LEPR, and TNF-α with endometrial receptivity was discussed. Results: GLUT4 was lower in the research group compared with control and normal groups, while LEPR and TNF-α were higher (P
Keywords: glucose transporter 4; leptin receptor; tumor necrosis factor-α; polycystic ovarian syndrome; infertility